Preliminary Studies on Citotoxicity and Genotoxicity Assessment of the PMMA-TiO2 Nanocompozites for Stereolithographic Complete Dentures Manufacturing - Totu, Eugenia Eftimie; Cristache, Corina Marilena; Isildak, Ibrahim; Yildirim, Ridvan; Burlibasa, Mihai; Nigde, Mustafa; Burlibasa, Liliana (CHIMINFORM DATA S A, 2018)
The aim of the present study was to characterize and preliminary assess the cytotoxicity and genotoxicity of different PMMA-TiO2 nanocomposites suitable to be used for two-parts stereolithographic complete denture manufacturing. In order to improve mechanical and antibacterial characteristics of the materials for 3D printing dentures, two matrix materials consisting in commercially available solutions of poly(methyl methacrylate) (PMMA), referred as dent-PMMA respectively base-PMMA, have been doped with different amount of TiO2 nanoparticles: 0.4, 0.6, 1.0, and 4.0% by weight. The obtained nanocomposites were structural characterized and assessed for antibacterial activity, cytotoxicity and genotoxicity. The newly obtained nanocomposites presented a good inhibitory action against the considered bacterial species-Staphylococcus aureus, good biocompatibility under 4.0% by weight. The results of the preliminary studies on cytotoxicity and genotoxicity assessment recommends the use of 0.4% TiO2 dent-PMMA and base-PMMA for CAD/CAM additive manufacturing of two-parts complete dentures/overdentures.
Keywords: TiO2-PMMA nanocomposites; 3D printing; cytotoxicity; genotoxicity; antibacterial activity; structural characterization; MANDIBULAR OVERDENTURE.; ATTACHMENT SYSTEMS; NANOCOMPOSITES; RESINS; Chemistry; Engineering